MANAGEMENT OF KITIBHA KUSHTA (PSORIASIS): A CASE STUDY (International Journal of Ayurveda and Pharma Research, 2018)
Now days society is more conscious about external beauty compare to internal beauty and also some professional fields they require good looking and charming beauty. Usually 10-15% cases present before general practitioners are pertaining to skin diseases. Due to altered life style, lack of physical exercise, unhygienic, mental stress, over eating, nutrition deficiency, skin diseases are commonly observed. Psoriasis is chronic disorder which is commonly encountered in day today’s clinical practices. It is one of the burning issues having social importance. Increased stress and sedentary life style are main predisposing factor which is accounting for wide spared prevalence of this disease. All the skin diseases in Ayurveda have been discussed under the broad heading of Kushta. Which are further divided in Mahakustha and Kshudra Kushta. This paper highlights a case study of Kitibha Kushta (Psoriasis) treated with the Ayurvedic principles in particular Shodhana Chikitsa.